The Chinese medicine Chai Hu Li Zhong Tang protects against non-alcoholic fatty liver disease by activating AMPKα. Issue 6 (7th November 2018) - Zhang, Meng; Yuan, Yuan; Wang, Qing; Li, Xiaobo; Men, Jiuzhang; Lin, Mingxin
Abstract : An effective treatment for non-alcoholic fatty liver disease (NAFLD) is urgently needed. In the present study, we investigated whether the Chinese medicine Chai Hu Li Zhong Tang (CHLZT) could protect against the development of NAFLD. Rats in an animal model of NAFLD were treated with CHLZT, and their serum levels of cholesterol (TC), triglycerides (TG), high density lipoprotein-cholesterol (HDL-C), low density lipoprotein-cholesterol (LDL-C), aspartate aminotransferase (AST), and alanine aminotransferase (ALT) were detected with an automatic biochemical analyzer. A cellular model of NAFLD was also established by culturing HepG2 cells in a medium that contained a long chain fat emulsion. Those cells were treated with CHLZT that contained serum from rats. After treatment, the levels of adenylate-activated protein kinase (AMPK) α (AMPKα), p-AMPKα, acetyl coenzyme A carboxylase (ACC) α (ACCα), pACCα, PPARγ, and SREBP-2 were detected. The AMPK agonist, acadesine (AICAR), was used as a positive control compound. Our results showed that CHLZT or AICAR significantly decreased the serum levels of TG, TC, LDL-C, AST, ALT, and insulin in NAFLD rats, and significantly increased their serum HDL-C levels. Treatments with CHLZT or AICAR significantly decreased the numbers of lipid droplets in NAFLD liver tissues and HepG2 cells. CHLZT and AICAR increased the levels of p-AMPKα and PPARγ in the NAFLD liver tissues and HepG2 cells, but decreased the levels of ACC-α, p-ACC-α, SREBP-2, and 3-hydroxyl-3-methylglutaryl-coenzyme A reductase (HMGR). CHLZT protects against NAFLD by activating AMPKα, and also by inhibiting ACC activity, down-regulating SREBP2 and HMGR, and up-regulating PPAR-γ. Our results suggest that CHLZT might be useful for treating NAFLD in the clinic.